2020
DOI: 10.1002/jia2.25654
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between physical and sexual violence and psychosocial health in young people living with HIV in rural South Africa

Abstract: Introduction Experiences of violence during youth contravene young people’s rights and increase the risk of depression and poor human immunodeficiency virus (HIV) care outcomes among youth living with HIV (YLWH). Intervention targets for mitigating the negative psychosocial effects of violence are needed, particularly in areas like rural South Africa where violence remains pervasive and mental healthcare is limited. This study aims to quantify the associations between physical and sexual violence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 83 publications
1
11
0
Order By: Relevance
“…Various screening tools based on different cut‐off scores were also used to measure depressive (Table 2) or anxiety symptoms (Table 3). These screening tools included the 9‐item patient health questionnaire [76] used in six studies [49,53,57,60,77, 78], the centre for epidemiologic studies depression scale [79] used in four studies [51,54,56,62], the child depression inventory [80] used in four studies [58,59,81,82], Beck’s depression inventory [83] used in three studies [48,61,84], the revised children’s depression rating scale [85] used by Kim et al . [28], the hospital anxiety and depression scale [86] used by Sale & Gadanya [47], Reynold’s adolescent depression Scale [87] used by Paul et al .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Various screening tools based on different cut‐off scores were also used to measure depressive (Table 2) or anxiety symptoms (Table 3). These screening tools included the 9‐item patient health questionnaire [76] used in six studies [49,53,57,60,77, 78], the centre for epidemiologic studies depression scale [79] used in four studies [51,54,56,62], the child depression inventory [80] used in four studies [58,59,81,82], Beck’s depression inventory [83] used in three studies [48,61,84], the revised children’s depression rating scale [85] used by Kim et al . [28], the hospital anxiety and depression scale [86] used by Sale & Gadanya [47], Reynold’s adolescent depression Scale [87] used by Paul et al .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐nine studies reported the prevalence of either major depression or depressive symptoms [45‐67,77,78,81]. Of these, seven studies [50,55,58,59,65,66,78] additionally reported the prevalence of anxiety or its symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations